Faktor-Faktor Yang Memengaruhi Minat Nasabah Dalam Menggunakan Layanan Mobile Banking Dengan Menggunakan UTAUT (Unified Theory Of Acceptance And Use Of Technology) (Studi Pada Pengguna Mobile Banking BRI KCP Universitas Brawijaya) - Arimbi Dewayanti; Ari Kusyanti; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Abstract Mobile banking is one of the e-banking services that provided by Bank which can facilitate all of the users to make transactions whenever and wherever for 24 hours and it can be accessed via smartphone. The purpose of this research is to determine the factors that influence of individual intention in using BRI's mobile banking services. These factors are Facilitating Conditions, Performance Expectancy, Social Influence, Effort Expetancy, Perceived Credibility, Perceived Financial Cost, Perceived Self Efficacy. The research model used in this research is UTAUT (Unified Theory of Acceptance and Use of Tehcnology). The collection of data was obtained by distributing questionnaires to 120 respondents using BRI's mobile banking services. The sampling technique used in this research is simple random sampling and for data processing using descriptive statistics to know the distribution and concentration of respondent's answer also using Kendal Tau (t) Correlation Test. The results of this research showed that individual intention in using BRI's mobile banking services influenced by Perceived Financial Costs, Facilitating Conditions, Performance Expectations, Perceived Self efficacy to Effort Expectancy, Perceived Self Efficacy, Social Influence, Effort Expectancy.